2005
DOI: 10.1038/sj.cgt.7700918
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Enhanced suppression of tumor growth using a combination of NK4 plasmid DNA-PEG engrafted cationized dextran complex and ultrasound irradiation

Abstract: This investigation aims to determine experimentally whether or not ultrasound (US) irradiation is effective in enhancing the in vivo gene expression of NK4 plasmid DNA and suppressing tumor growth. NK4, composed of the NH 2 -terminal hairpin and subsequent four-kringle domains of hepatocyte growth factor (HGF), acts as an HGF-antagonist and angiogenesis inhibitor. Dextran was cationized by introducing spermine to the hydroxyl groups to allow for polyionic complexation with NK4 plasmid DNA. The cationized dextr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 53 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…Animal study also confirmed that HGC nanoparticles could be used as a potent gene delivery vehicle in vivo [44]. The complexation with poly (ethylene glycol) (PEG) -engrafted cationized dextran in combination with ultrasound (US) irradiation is a promising way to target the NK4 plasmid DNA to the tumor for gene expression [45]. Therefore, developments of ORF nanparticles are underway in our laboratory to for achieving efficient supplementation delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Animal study also confirmed that HGC nanoparticles could be used as a potent gene delivery vehicle in vivo [44]. The complexation with poly (ethylene glycol) (PEG) -engrafted cationized dextran in combination with ultrasound (US) irradiation is a promising way to target the NK4 plasmid DNA to the tumor for gene expression [45]. Therefore, developments of ORF nanparticles are underway in our laboratory to for achieving efficient supplementation delivery.…”
Section: Discussionmentioning
confidence: 99%
“…These cationic polysaccharides were prepared by reductive amination of the oligoamine and periodate-oxidized polysaccharides. Although most of these cationic conjugates formed stable complexes with pDNAs as determined by ethidium bromide quenching assay, only the dextran-spermine- (D-SPM- ) based polycations were found to be highly effective in transfecting various cell lines [2531]. Dextran-spermine conjugates have also been modified with increasing amounts of polyethylene glycol chains (PEG).…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that the dextran-spermine based polycations have been found to be highly effective as nonviral vectors in transfecting many different cells in vitro. [11][12][13][14][15][16][17] Our recent study also demonstrated that electrospun poly (glycolic acid) (PGA)/ collagen nanofibers significantly enhanced cell adhesion compared with PGA/collagen microfibers. 18 Based on these results, the present study aims to fabricate a tissue-like 3D transgene cell construct for use as a therapeutic cell-based gene delivery system or as an in vitro model system for testing genetic manipulations to understand the effects of gene expression on tissue development.…”
Section: Introductionmentioning
confidence: 99%